2010
DOI: 10.1073/pnas.1007487107
|View full text |Cite
|
Sign up to set email alerts
|

Quaking I controls a unique cytoplasmic pathway that regulates alternative splicing of myelin-associated glycoprotein

Abstract: Precise control of alternative splicing governs oligodendrocyte (OL) differentiation and myelination in the central nervous system (CNS). A well-known example is the developmentally regulated expression of splice variants encoding myelin-associated glycoprotein (MAG), which generates two protein isoforms that associate with distinct cellular components crucial for axon-glial recognition during myelinogenesis and axon-myelin stability. In the quakingviable (qk v ) hypomyelination mutant mouse, diminished expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
79
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(86 citation statements)
references
References 46 publications
(85 reference statements)
7
79
0
Order By: Relevance
“…Together, the data reveal a specific interaction between hnRNP A1 and the Mag exon 12 5 ′ splice site, and suggest that binding of hnRNP A1 may interfere with U1 snRNP association. Our observations of an interaction between hnRNP A1 and Mag RNA is consistent with the observation by Zhao et al (2010) that the Mag pre-mRNA coimmunoprecipitates with hnRNP A1.…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…Together, the data reveal a specific interaction between hnRNP A1 and the Mag exon 12 5 ′ splice site, and suggest that binding of hnRNP A1 may interfere with U1 snRNP association. Our observations of an interaction between hnRNP A1 and Mag RNA is consistent with the observation by Zhao et al (2010) that the Mag pre-mRNA coimmunoprecipitates with hnRNP A1.…”
Section: Resultssupporting
confidence: 81%
“…NMD generally requires a spacing of 50-55 nucleotides between the stop codon and the exon junction for efficient degradation (Nagy and Maquat 1998); in Mag exon 12, only 12 nucleotides are present. Recently, Feng and coworkers reported that hnRNP A1 enhances Mag exon 12 inclusion in HEK293T cells through an interaction with an element within exon 13 (Zhao et al 2010). The splicing reporter used in the current study does not include this exon.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, QKI proteins can indirectly regulate AS through the modulation of other splicing regulators. Specifically, QKI-6, a cytoplasmic variant encoded by the qk locus, represses the translation of hnRNPA1, which, in turn, regulates MAG exon 12 AS (Zhao et al 2010). Several other transcripts encoded by genes relevant to myelin formation and maintenance display altered splicing patterns in Quaking mice (Wu et al 2002).…”
Section: Additional Neural-specific Splicing Regulatorsmentioning
confidence: 99%
“…QKI proteins are members of signal transduction and activation of the RNA (STAR) family that play an essential role in OL development (36). These proteins, such as MBP, myelin-associated glycoprotein, and actin-interacting protein 1, control the splicing and stability of mRNA that are crucial to OL differentiation (37). The RNA-binding activity of QKI is governed by Fyn kinase (38,39), which is linked with PIKE function (9,40).…”
Section: Ol-derived Integrin and Axon-derived Lamin That Activates Akmentioning
confidence: 99%